A person is not a number: Discourse involvement in subject–verb agreement computation - Mancini, Simona; Molinaro, Nicola; Rizzi, Luigi; Carreiras, Manuel (Brain research, 2011)
Agreement is a very important mechanism for language processing. Mainstream psycholinguistic research on subject–verb agreement processing has emphasized the purely formal and encapsulated nature of this phenomenon, positing an equivalent access to person and number features. However, person and number are intrinsically different, because person conveys extra-syntactic information concerning the participants in the speech act. To test the person-number dissociation hypothesis we investigated the neural correlates of subject–verb agreement in Spanish, using person and number violations. While number agreement violations produced a left-anterior negativity followed by a P600 with a posterior distribution, the negativity elicited by person anomalies had a centro-posterior maximum and was followed by a P600 effect that was frontally distributed in the early phase and posteriorly distributed in the late phase. These data reveal that the parser is differentially sensitive to the two features and that it deals with the two anomalies by adopting different strategies, due to the different levels of analysis affected by the person and number violations. ► Person and number have different interpretive properties. ► Person violations elicited an N400 effect and a P600. ► Number violations elicited a LAN-P600 pattern. ► The parser is differentially sensitive to the two features.